(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This thesis examines the role of women in literature through the lens of feminist theory, focusing on the contributions of feminist writers and their impact on literary discourse. It explores how feminist literature challenges traditional narratives, redefines female representation, and addresses gender inequalities within literary traditions. By analyzing key feminist texts and the evolution of feminist literary criticism, this study provides insights into the ways feminist writers have reshaped the literary landscape and advocated for gender equity.